Public capital and economic growth: A critical survey - Ward E. Romp; Jakob de Haan (EIB Papers, 2005)
This paper provides an overview of both theoretical and empirical literature on the link between public investment (capital) and economic growth (national income). We first survey the channels through which public capital can conceivably affect growth. We then turn to reviewing the existing empirical literature, and we conclude that although not all studies find a growth-enhancing effect of public capital, there is now more consensus than in the past that public capital furthers economic growth. However, the impact reported by recent studies is not as big as some earlier studies suggested. We conclude with an overview of what is known about the optimality of public capital stocks.
Keywords: 330; Öffentliche Investition; Wirtschaftswachstum; Theorie; Welt